Feynman’s interpretation of quantum theory - Zeh, Heinz-Dieter (The European physical journal. H, Historical perspectives on contemporary physics, 2011)
A historically important but little known debate regarding the necessity and meaning of macroscopic superpositions, in particular those containing different gravitational fields, is reviewed and discussed from a modern perspective.